OSMANLI İDARESİNDE MUSUL (1532-1639) - GÜNDÜZ, AHMET (Fırat Üniveristesi, 1998)
This study was carried out on the political, administrative, economical, demographic situation of Mosul between 1523-1639. Foundation of Mosul goes back to 2000 BC and lots of nations dominated the town throughout the history. Turks began to settle down this region in 1040s. Mosul and its surrounding was entirely dominated by Turks from 1096 on and continued up to the third of November 1918. After conquering Mosul from Safevis, Ottomans governed this town first in the status of sanjaq and from 1586 on governed as province. Mosul was situated just on the right bank of the Tigris and was surrounded by ramparts. The number of quarter varied between 20 and 27 in 1523-1575, four of them were Christian quarters, one was Jewish quarter, and the rest were Moslem quarters. Due to its geographical location, Mosul maintained its commercial and industrial vividness in every period. In 1523 income-tax was 1,5 million.in 1540; 2,2 million, in 1557; 3,6 million and in 1575; 3,8 million akçe. The population of Mosul rose from 15160 to 22403 between 1523-1575. % 68- 74 of this population were Moslems, % 26-32 were non-Moslems. Another aspect of Mosul that it was a town of foundation. Because there were about 65 social foundations such as mosques, small mosques, theological schools, dervish lodges. Consequently from the point of population, cultural structure, and sight; Mosul has the same characteristic like the other towns of Anatolia.
Mosul under domination of Ottoman (1532-1639)
Keywords: Tarih; History